Effects on cardiorespiratory fitness of moderate-intensity training vs. energy-matched training with increasing intensity - Reuter, Marcel; Rosenberger, Friederike; Barz, Andreas; Venhorst, Andreas; Blanz, Laura; Roecker, Kai; Meyer, Tim (Frontiers in Sports and Active Living, 2024)
Introduction: The present study investigated the role of training intensity in the dose-response relationship of endurance training on cardiorespiratory fitness (CRF). The hypothesis was that beginners would benefit from an increase in training intensity after an initial training phase, even if the energy expenditure is not altered. For this purpose, 26 weeks of continuous moderate training (CON) was compared to training with gradually increasing in intensity (INC) but constant energy expenditure.Methods: Thirty-one healthy, untrained subjects (13 men, 18 women; 46 ± 8 years; BMI 25.4trained 10 weeks with moderate intensity (3 d•wk - 1 for 50 min•session -1 at 55% HRreserve) before allocation to one of two groups. A minimization technique was used to ensure homogeneous groups. While group CON continued with moderate intensity for 16 weeks, INC trained with 70% HRreserve for 8 weeks and thereafter a 4x4 training (HIIT) for 8 weeks. Constant energy expenditure was ensured by indirect calorimetry and corresponding adjustment of training volume. Treadmill tests were performed at baseline, after 10, 18 and 26 weeks.Results: INC improved VO2max (3.4±2.7mL•kg -1 •min -1 ) significantly more than CON (0.4±2.9 mL•kg -1 •min -1 ) (P = .020). Additionally, INC improved Vmax (1.7±0.7 km•h -1 ) significantly more than CON (1.0±0.5 km•h -1 ) (P = .001). Reduction of resting HR was significantly larger in INC (7±4 bpm -1 ) than in CON (2±6 bpm -1 ) (P = .001). The mean heart rate of the submaximal exercise test was reduced significantly in CON (5±6 b•min -1 ; P = .007) and in INC by (8±7 b•min -1 ; P = .001), without significant between-group interaction. Conclusion: Increasing intensity leads to greater adaptations in CRF than a continuing with moderate intensity even without increased energy expenditure. After 26 weeks of training in the moderate and higher intensity domain, energy-matched high-intensity interval training (HIIT) elicited further adaptations in cardiorespiratory fitness. Thus, training intensity plays a crucial role in the dose-response relationship of endurance training in untrained and healthy individuals.